2010
DOI: 10.1007/s10705-010-9408-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from fertilized and unfertilized grasslands on peat soil

Abstract: Emissions of nitrous oxide (N 2 O) from managed and grazed grasslands on peat soils are amongst the highest emissions in the world per unit of surface of agriculturally managed soil. According to the IPCC methodology, the direct N 2 O emissions from managed organic soils is the sum of N 2 O emissions derived from N input, including fertilizers, urine and dung of grazing cattle, and a constant 'background' N 2 O emission from decomposition of organic matter that depends on agro-climatic zone. In this paper we q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 23 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…The functions of N and water addition in improving soil N 2 O effluxes are described as follows: (1) N input provides sufficient substrate for the N 2 O generation processes; (2) the drying-rewetting transformation after water addition allows the release of several organic and inorganic substances into the soil, which provides sufficient substrates and energy for nitrification and denitrification (Mummey et al, 1994;Bollmann and Conrad, 1998;Beare et al, 2009); and (3) the variations in soil NO 3 À and NH 4 + contents suggest that water addition facilitates the immediate transfer of fertilizers to mineral N from surface soil to the 0-10 cm soil layer, which also provides ample substrate for nitrification and denitrification (Goldberg et al, 2010;Kim et al, 2010). Short bursts of N 2 O emissions after fertilization were also observed in previous studies (Dobbie and Smith, 2003;Jones et al, 2007); however, the highest effluxes observed in our study was in the lower range relative to the peak values of N 2 O obtained by some other N addition experiments in temperate grasslands abroad (ranged from 100 to 7500 mg m À2 h À1 N 2 O-N) (e.g., Kim et al, 2010;Pinto et al, 2004;Van Beek et al, 2011). In this study, the highest peak efflux among different treatments was only (Peng et al, 2011).…”
Section: Main Influence Factors On N 2 Effluxes Under Water and N Addsupporting
confidence: 82%
“…The functions of N and water addition in improving soil N 2 O effluxes are described as follows: (1) N input provides sufficient substrate for the N 2 O generation processes; (2) the drying-rewetting transformation after water addition allows the release of several organic and inorganic substances into the soil, which provides sufficient substrates and energy for nitrification and denitrification (Mummey et al, 1994;Bollmann and Conrad, 1998;Beare et al, 2009); and (3) the variations in soil NO 3 À and NH 4 + contents suggest that water addition facilitates the immediate transfer of fertilizers to mineral N from surface soil to the 0-10 cm soil layer, which also provides ample substrate for nitrification and denitrification (Goldberg et al, 2010;Kim et al, 2010). Short bursts of N 2 O emissions after fertilization were also observed in previous studies (Dobbie and Smith, 2003;Jones et al, 2007); however, the highest effluxes observed in our study was in the lower range relative to the peak values of N 2 O obtained by some other N addition experiments in temperate grasslands abroad (ranged from 100 to 7500 mg m À2 h À1 N 2 O-N) (e.g., Kim et al, 2010;Pinto et al, 2004;Van Beek et al, 2011). In this study, the highest peak efflux among different treatments was only (Peng et al, 2011).…”
Section: Main Influence Factors On N 2 Effluxes Under Water and N Addsupporting
confidence: 82%
“…The HB soil texture was classified as a clay loam (gleysol) and was imperfectly drained with evidence of gleying (at 0.3m depth). In addition, drainage impeded soils tend to be low in oxygen and tend to lose a greater percentage of N as N 2 O (Dennis et al, 2012) compared to well drained soils, with emissions from managed and grazed grasslands on peat soils among the highest emissions in the world (van Beek et al, 2011). Results from the current study demonstrated that emissions from CAN at HB were significantly higher than the other two sites, probably due to the higher denitrification potential of these soils combined with higher precipitation at this location especially in 2013.…”
Section: The Effect Of N Formulation On N 2 O Emissionsmentioning
confidence: 99%
“…However, whilst the results are from three different studies, the data are collected from the same peatland area. Furthermore, during the critical appraisal process, these studies were classified as unclear [63,64] and high [65] in their susceptibility to bias. The results should therefore be treated with caution.…”
Section: Dry-vs-wetmentioning
confidence: 99%